Heterogeneity of cough neurobiology: Clinical implications. (April 2019) - Mazzone, Stuart B.; Farrell, Michael J.
Abstract: Cough is an important protective mechanism for clearing the airways but becomes a troublesome, and often difficult to treat, symptom in respiratory disease. Although cough can be produced as a reflex in response to the presence of irritants within the airways, emerging research demonstrates an unappreciated complexity in the peripheral and central neural systems that regulate cough. This complexity includes multiple primary sensory neurons that can induce or facilitate reflex coughing, different ascending central circuits in the brain that contribute to cough sensory discrimination and the perception of the urge-to-cough, and several descending brain systems for inducing, facilitating and inhibiting cough responses. Consequently, the mechanisms responsible for cough becoming dysregulated in disease are not likely homogeneous across all patients with chronic cough. The available data suggests that changes in primary sensory neuron excitability, altered central nervous system integration of sensory inputs and changes in descending control mechanisms may each contribute to the development of cough hypersensitivity.